A and d seem correct to me.
b and c are definitely wrong.
Answer:
x = -1,5
Step-by-step explanation:
2x² - 8x - 10
2x² - 10x + 2x - 10
2x(x - 5) + 2(x - 5)
(x - 5)(2x + 2)
x = 5 x = -2/2
x = -1,5
My guess is that you're doing the Law of Cosines? You have everything you need for that except the angle theta, which is the thing you need to find. It's set up like this: (8)^2 = (10)^2 + (5)^2 -[2(10)(5)cos A] I used A instead of theta. Doing that math, you have: 64 = 100 + 25 -[ 100 cos A]; 64 = 125 - 100 cos A;
-61 = - 100 cos A; -61 / -100 = cos A; .61 = cos A. Now use your inverse function on your calculator to find cos^-1(.61) and that equals 52.4
Answer:
g(x) = - x² - x + 12
Step-by-step explanation:
Given
g(x) = (- x - 4)(x - 3)
Each term in the second factor is multiplied by each term in the first factor, that is
- x(x - 3) - 4(x - 3) ← distribute both parenthesis
= - x² + 3x - 4x + 12 ← collect like terms
= - x² - x + 12 ← in standard form
Answer:
6 cm.
Step-by-step explanation:
Since they've given use the area of the triangle, we can use the area formula to find the base of the triangle.
The formula to find the area of a triangle is:
a= 1/2hb
h = height
b= base
We know:
a=24
h=8